Seismic Fragility Curves for Reinforced Concrete Dual System Buildings: Pearl Tower as Case Study - Ismael, Sarwar S.; Ahmed, Faris R. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
A seismic fragility curve is a visual representation that illustrates the likelihood of a structure surpassing a particular damage or performance limit state caused by an earthquake with a specific intensity or ground motion level. This curve is typically generated using probabilistic seismic hazard analysis and structural reliability analysis methods. It is based on statistical models that rely on past earthquake data and simulations of future earthquake scenarios to predict the structure or system’s behavior under seismic forces. In this study, the seismic performance of 30 stories of 95 m height dual system reinforced concrete buildings located in Erbil is evaluated by analyzing three distinct ground motions. A non-linear platform is used to simulate and analyze data, followed by the generation of seismic inter-story drift fragility curves using Incremental Dynamic Analysis. The buildings’ seismic structural performance is assessed based on five different performance levels, including operational phase, immediate occupancy, damage control, life safety, and collapse prevention (CP). Each level is associated with different levels of damage and corresponding degrees of functionality and safety. The fragility curves show that the building has a 50% chance of achieving or exceeding the (CP) level with highly intense ground vibrations with peak ground acceleration = 1.6 g. In addition, these curves can be beneficial in creating future local design codes and provide significant support in evaluating the seismic performance of existing buildings.